Linking quantitative demands to offshore wind workers’ stress: do personal and job resources matter? A structural equation modelling approach - Janika Mette; Marcial Velasco Garrido; Alexandra M. Preisser; Volker Harth; Stefanie Mache (BMC Public Health, 2018)
Abstract Background Employees in the offshore wind industry are exposed to various job demands, increasing the workers’ risk of experiencing strain reactions. However, personal and job resources might play a role in the stressor-strain context. The aim of this study was (1) to examine the link between offshore employees’ quantitative demands and stress, and (2) to study the role of personal and job resources (psychological detachment from work, social support, and influence at work) in this stressor-strain relationship. Methods Two hundred fifty offshore wind workers responded to an anonymous web-based survey, assessing the workers’ quantitative demands, social support, influence at work, psychological detachment from work, and stress. Descriptive statistical analyses and structural equation modelling were applied to test the hypotheses. Results Correlation analyses revealed substantial associations between employees’ quantitative demands, personal and job resources, and stress. Results of structural equation modelling indicated a good fit of the hypothesized model. Quantitative demands were positively related to stress, and psychological detachment from work partially mediated this relationship. Social support was negatively related to stress, while influence at work was not. Neither social support nor influence at work moderated the stressor-strain or stressor-detachment relationship. Conclusions The results contribute to the current knowledge on the topic. They can be used to design health promotion interventions aimed at reducing offshore employees’ quantitative demands, fostering their ability to mentally detach from work, and enhancing social support at the offshore workplace.